Tourism Industry Competitiveness of Semarang Municipality - Hertiana Ikasari; Ida Farida (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
This study aims to analyze competitiveness level of tourism industry in Semarang Municipality. The data used in this research are secondary data from Central Bureau of Statistics (CBS/BPS) and Culture and Tourism Office of Semarang Municipality. Moreover, this study uses an analytical tool, i.e competitiveness monitor (CM) method. The result shows that Semarang Municipality has several lower indicators of competitiveness calculation than Surakarta Municipality and Magelang Regency, i.e. Human Tourism Indicator (HTI), Environment Indicator (EI), and Human Resources Indicator (HRI). On the other hand, Semarang Municipality also has some higher competitiveness calculation indicators compared to that of Surakarta Municipality and Magelang Regency in Price Competitiveness Indicator (PCI), Infrastructure Development Indicator (IDI), Openness Indicator (OI) and Social Development Indicator (SDI). The improvement of tourism competitiveness in Semarang Municipality requires synergy from many parties, including the government, business actors in tourism sector (hotel owners, travel bureaus), private sector and academics.